Your next Move : The Leader's Guide to Navigating Major Career Transitions - Watkins, Michael D. (Boston Harvard Business Press, 2009)
After three months in a new job, are you up to speed? Will you sink ...or swim? Transitions into new roles are the crucibles in which leaders get their toughest tests, and they're the defining factor in professional careers today. This title shows how you can survive and thrive in all the major transitions you may face during your career.
Keywords: Management -- Promotions -- Career development